INOVASI PEMBELAJARAN MATEMATIKA SEKOLAH DASAR BERBASIS KEBUDAYAAN SEKITAR : RUMAH SANDI NEGARA KULON PROGO - Agus Santoso; Sutrisna Wibawa; Supriyoko (Tuladha : Jurnal Pendidikan Dasar, 2023)
This development research aims to develop and produce mathematical worksheets based on the surrounding culture with flat-shaped materials. This study uses a Research and Development (R&D) model that can produce certain products and involves several validators as testers of the validity of the product. The subjects in this study were fifth grade students at SD N Purwoharjo. Data collection techniques using validation sheets and questionnaire methods. The results of the initial observations made by the researchers showed that so far teachers have not developed LKPD. Local wisdom-based education is education that teaches students to always be attached to the concrete situations they face. The National Sandi House is an old house that was used as a code house during the Dutch military aggression II in Yogyakarta. In the past, this house-shaped site was used by ciphers to operate secret ciphers, without the knowledge of the Dutch. The development of LKPD was declared valid by the validator with an average yield of 94.485%, indicating that habit-based LKPD is very feasible to apply in learning. The response of the students obtained was to show a positive response. This is in accordance with the results of the practicality test of LKPD based on the surrounding culture which was implemented at SD N Purwoharjo in grade V, which was stated to be valid and practical.